2014
DOI: 10.1556/aphysiol.101.2014.007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antioxidant enzymes and lipid peroxidation in extensor digitorum longus muscles of streptozotocin-diabetic rats may contribute to muscle atrophy

Abstract: We investigated muscle atrophy, major antioxidant enzymes and lipid peroxidation in the extensor digitorum longus (EDL, predominantly fast fibers) and soleus (predominantly slow fibers) muscle of streptozotocin-diabetic rats. Female Wistar rats were divided into a control (n = 5) and streptozotocin-induced diabetic group (n = 5). Eight weeks after diabetes induction the EDL and soleus muscles were removed and catalase (CAT), glutathione peroxidase (GPX) and superoxide dismutase activity (SOD), and thiobarbitur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…In contrast, muscle weight was decreased in both the DM and DM + HS groups. Moreover, the body weight of rats in the DM and DM + HS groups decreased; these results are consistent with the findings of previous studies on STZinduced diabetic rats (1,11). It is well known that muscle weight is influenced by body weight.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, muscle weight was decreased in both the DM and DM + HS groups. Moreover, the body weight of rats in the DM and DM + HS groups decreased; these results are consistent with the findings of previous studies on STZinduced diabetic rats (1,11). It is well known that muscle weight is influenced by body weight.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous study, we demonstrated that oxidative stress is increased in the EDL muscles of STZ-induced diabetic rats (11). Heat stress provides protection against oxidative stress and preserves muscle mass during hind limb immobilization (17).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The rats were randomly divided into four groups consisting of six animals per group as follows: control (Con), HS, diabetes mellitus (DM), and diabetes mellitus and heat stress (DM+HS). Diabetes was induced by a single intraperitoneal injection of STZ (50 mg/kg body weight; Wako Pure Chemical Industries, Ltd., Osaka, Japan) dissolved in physiological saline according to a previous study (Nonaka et al 2014).…”
Section: Animalsmentioning
confidence: 99%